Treatment of Rheumatoid Arthritis with Fenoprofen: Comparison with Aspirin. Issue 5900 (2nd February 1974) - Huskisson, E. C.; Wojtulewski, J. A.; Berry, H.; Scott, Jane; Hart, F. Dudley; Balme, H. W.
Abstract : Fenoprofen, a compound with analgesic, anti-inflammatory, and antipyretic properties in animals, has been compared with placebo in a double-blind cross-over trial in 60 patients with rheumatoid arthritis. There was a statistically highly significant reduction in pain, duration of morning stiffness, analgesic requirements, and articular index, with increase in grip strength. There was no significant reduction in joint size or temperature. In a subsequent double-blind group-comparative study fenoprofen proved to be as effective as aspirin in relieving the symptoms of rheumatoid arthritis, with strikingly fewer side effects. Almost half of the patients taking aspirin were unable to tolerate the drug in adequate dosage for six months. The remainder were able to take on average only 4 g daily, and at this dose almost half still complained of tinnitus and deafness. Fenoprofen is likely to be useful for patients who cannot tolerate aspirin and other more toxic anti-inflammatory drugs or whose disease is not of sufficient severity to justify their use.